General Strategy for Fabrication of Ordered One Dimensional Inorganic Structures by Electrospinning: Structural Evolution From Belt to Solid via Hollow Tubes. Issue 4 (26th January 2021) - Senthamizhan, Anitha; Balusamy, Brabu; Celebioglu, Asli; Uyar, Tamer
Abstract : Super‐structured hollow materials are the subject of intense research due to their attracting properties and diverse applications. Despite their significance, it still remains a crucial challenge to develop a simple and well‐organized method to prepare the hollow tubes with controlled architectures. Herein, a general route to prepare structurally well‐defined 1D zinc oxide (ZnO) structures by a single‐spinneret electrospinning method coupled with thermal treatment is demonstrated for the first time and subsequently designated to identify high‐performance materials for catalytic application. Two critical factors including tailoring the precursor amount and colloidal‐stability of the precursor play critical role in tuning the structure precisely. The careful optimization of processing conditions enables chronological structural evolution from tubular to solid fiber structures composed of nanograins. These ZnO complex hollow structures showcase excellent photocatalytic performance; single nanograined wall hollow tubes manifest the high‐catalytic performance over other samples with remarkable cycling stability. Benefitting from fabrication adaptability, different types of metal oxide hollow tubes are prepared that indicates the generality of the method. The proposed method postulates new insights for the development of electrospun hollow‐structured fibers in a simple, cost‐effective, and industrially feasible manner which holds apparent potential in many sectors. Abstract : A general strategy for the fabrication of 1D hollow‐structured materials with complex architectures via a single‐spinneret electrospinning method is demonstrated and subsequently designated to identify the high‐performance material for catalytic application.